A review of the winter influenza strategy for hospitals within a major district health board in New Zealand following the 2012 Influenza season - Schousboe, Mona; Jennings, Lance C (International Journal of Infection Control, 2013)
Abstract Winter influenza planning is an integral part of a health services preparation for the annual increase in respiratory virus infections and associated hospital admissions in New Zealand. A moderate to severe influenza A (H3N2) outbreak occurred in the winter of 2012 resulting in an unprecedented number of attendances of patients with influenza-like illness at the Canterbury District Health Board (CDHB) hospital’s emergency assessment areas. A review of the hospital winter influenza strategy following this outbreak, included the use of dedicated influenza wards, extensive diagnostic testing of patients, infection control advice, staff influenza vaccination and the use of Oseltamivir for treatment of patients and prophylaxis of their contacts. The review found that 534 patients were seen and laboratory confirmed to have influenza, 347 patients were admitted and 40 nosocomial influenza infections recorded over an 11 weeks period. The strategy contributed to the management of the hospital admission of patients with influenza, a relatively low number of nosocomial influenza infections in the dedicated admission wards and low in-hospital mortality. The use of diagnostic testing for influenza with planned escalation of services supported the clinical decision to treat patients with confirmed influenza and prophylaxis contacts with Oseltamivir probably facilitated appropriate discharge of patients.